PENGARUH KOMUNIKASI INTERN TERHADAP SEMANGAT KERJA PEGAWAI RUMAH SAKIT UMUM (RSUD) DR. H. CHASAN BOESOEIRIE TERNATE - Safri Basir; Zulkifili Zulkifili; Nurlaila Nurlaila (Jurnal Manajemen Sinergi, 2015)
This research aim to to know the influence of communications intern to spirit ofofficer job by partial or visible individually at calculation result analyses the doubled linearregression, inferential that variable of communications intern have an effect on the significantto spirit ofPublic Hospital officer job] of Area ( RSUD) Dr. H. Chasan Boesoirie Ternate.Result of analysis of correlation coefficient in this research, there are strong positive relationbetween communications intern hotly work officer. This is visible from value of coefficientdeterminantnt (R2). Or can be told by there are influence of between variable ofcommunications intern to spirit of Public Hospital officer job of Area ( RSUD) Dr. H. ChasanBoesoirie Ternate.